1999
DOI: 10.1021/bi990927f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Heterogeneity of the Bacteriopheophytin Electron Acceptor HA in Reaction Centers from Rhodopseudomonas viridis Revealed by Fourier Transform Infrared Spectroscopy and Site-Directed Mutagenesis

Abstract: The light-induced Fourier transform infrared (FTIR) difference spectra corresponding to the photoreduction of either the HA bacteriopheophytin electron acceptor (HA-/HA spectrum) or the QA primary quinone (QA-/QA spectrum) in photosynthetic reaction centers (RCs) of Rhodopseudomonas viridis are reported. These spectra have been compared for wild-type (WT) RCs and for two site-directed mutants in which the proposed interactions between the carbonyls on ring V of HA and the RC protein have been altered. In the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…The strongest peak at 1697 cm −1 can hence be attributed to the overlap of the H-bonded C=O band downshifted by 10 cm −1 from 1707 cm −1 and the non-H-bonded band that remained at 1695 cm −1 . A similar example of the coexistence of H-bonded and non-H-bonded forms has been observed in the 13 2 -ester C=O of the bacteriopheophytin electron acceptor in PbRC 49 . The equilibrium of 2 H-bonded forms at the keto C=O in P840 + seems absent in neutral P840 of the V689C RC, because the original WT band at 1682 cm −1 , which reflects a non-H-bond interaction, did not remain in the spectrum of the V689C RC.…”
Section: Discussionsupporting
confidence: 68%
“…The strongest peak at 1697 cm −1 can hence be attributed to the overlap of the H-bonded C=O band downshifted by 10 cm −1 from 1707 cm −1 and the non-H-bonded band that remained at 1695 cm −1 . A similar example of the coexistence of H-bonded and non-H-bonded forms has been observed in the 13 2 -ester C=O of the bacteriopheophytin electron acceptor in PbRC 49 . The equilibrium of 2 H-bonded forms at the keto C=O in P840 + seems absent in neutral P840 of the V689C RC, because the original WT band at 1682 cm −1 , which reflects a non-H-bond interaction, did not remain in the spectrum of the V689C RC.…”
Section: Discussionsupporting
confidence: 68%
“…sphaeroides reaction centers, termed H L1 -and H L2 - (58,59). The relevance of these conformations to relaxation processes and the energetics of primary electron transfer have been discussed (58)(59)(60). It was suggested that the H L1 -state, with φ Ac ) 45°or 315°(i.e., -45°), and the H L2 -state, with φ Ac ) 135°or 225°(i.e.…”
Section: Ubiquinone Exclusion At the Q A Sitementioning
confidence: 99%
“…In particular, numerous studies focused on the assignment of hydrogen bonds to the 9-keto and 2-acetyl groups because they are part of the delocalized π-system and any change in H-bonding is expected to affect the redox properties of the chromophores and hence, ET rates . Light-minus-dark FTIR difference spectroscopy, pioneered by Breton et al , allows for the assignment of the carbonyl frequencies of the chromophores in the part of the RC, where ET occurs (P L , B L , H L , Q A , and Q B ). ,, Vibrational frequencies of the chromophores in the inactive M-branch (P M , B M , and H M ) cannot be assigned using this method. In contrast, resonance Raman techniques enable assignment of the carbonyl modes of all chromophores because the ground electronic absorption spectrum shows well-enough resolved bands for all chromophores at low temperature allowing for selective enhancement of vibrational modes of each individual chromophore. , …”
Section: Discussionmentioning
confidence: 99%
“…In particular, numerous studies focused on the assignment of hydrogen bonds to the 9-keto and 2-acetyl groups because they are part of the delocalized π-system and any change in H-bonding is expected to affect the redox properties of the chromophores and hence, ET rates. 44 Light-minus-dark FTIR difference spectroscopy, pioneered by Breton et al 21,45 allows for the assignment of the carbonyl frequencies of the chromophores in the part of the RC, where ET occurs (P L , B L , H L , Q A , and Q B ). 5,21,45 Vibrational frequencies of the chromophores in the inactive M-branch (P M , B M , and H M ) cannot be assigned using this method.…”
Section: Discussionmentioning
confidence: 99%